Rapid conversion to virtual obesity care in COVID‐19: Impact on patient care, interdisciplinary collaboration, and training. (28th August 2021) - Lohnberg, Jessica A.; Salcido, Lianne; Frayne, Susan; Mahtani, Naina; Bates, Cheryl; Hauser, Michelle E.; Breland, Jessica Y.
Abstract: Objective: The COVID‐19 pandemic presents challenges to maintaining interdisciplinary collaboration while transitioning care to telehealth environments. This paper describes how an intensive weight management clinic rapidly transitioned from in‐person only to a telehealth environment. Method: As a program evaluation project, changes to clinic procedures were tracked on a weekly basis. Patients were invited to complete phone surveys after clinic appointments from 1 May 2020 to 31 July 2020. The survey included 12 items rated on a 5‐point scale ("strongly disagree" to "strongly agree"). Results: Adaptations included converting team meetings and clinical training to phone/video platforms and transferring a complex patient tracking system to an interactive virtual format. Fifty‐eight patients completed phone surveys (81% response rate). All "agreed" or "strongly agreed" that they were satisfied with telehealth care; 51% "agreed" or "strongly agreed" that telephone visits were as good as in‐person visits; and 53% preferred phone appointments even after pandemic restrictions are eased. Conclusions: It is feasible to rapidly transition to a telehealth clinic when supported by infrastructure and resources of a national, integrated healthcare system. Patient preferences include access to both telehealth and in‐person services. A blended telehealth/in‐person model that maintains interdisciplinary collaboration and training is necessary even after the COVID‐19 pandemic.